Pengembangan Model Konseptual Transfer Pengetahuan dari Perguruan Tinggi Ke Industri Kecil - Retno Indriartiningtias; Iwan Inrawan Wirajmadja (Jurnal Teknik Industri, 2009)
Small industries is once of the informal sector that can solve employee’s problems. The small industries main problems in indonesia is unknowledgeable. This point is the importantweakness of the small industries in Indonesia. For this purpose, it needs institutions to make the small industries in Indonesia knowledgeable with knowledge transfer program. One of the institution is university. University as the center of knowledge, have to does the knowledge transfer effectively. Based on this problem, it needs to build the effectiveness of knowledge transfer model. This paper is a begining research that has a purpose to build the model of knowledge transfer from University to Small Industries. As a beginning research this paper uses literature study for building the model and interview for validating. Based on literature study, the  conceptual model was built from 6 (six) dimensions as key factors of knowledge transfer (endogenous variables) (characteristics of university, characteristics of small industries,characteristics of media, characteristics of knowledge,  characteristics of environment and the effectiveness of knowledge transfer) and 29 exogenous variables. The model was validated by enterviews with expert from Trunojoyo University and the owner of Small Industry in Bangkalan. From validating, the model was built from 6 endogenous variabels 26 exogenous variables.